The dynamics of the economic potential of the multinational corporation Google in years 2001−2009 - Boguś, Marta (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2011)
The predominant role played by the multinational corporations comes as a result of the globalization processes. These corporations can be distinguished by their significant economic potential which is often greater than the economic potential of many countries. The Google corporation was established in 1998 by Larry Page and Sergey Brin. Due to their strategy based on innovation, human potential and high quality standards, Google has developed rapidly and became a leader in cloud computing and Internet search. According to the ranking conducted by The Global 2000 Magazine in 2009 Google was placed on 9th position out of 123 computing corporations. When it comes to its market value, Google has taken 3rd position after Microsoft and Apple. As a result of the analysis of their economic potential between 2001−2009, based on revenue, profit, assets, market value and the number of employees, we can identify three phases in the company’s development. The initial period in years 2001−2004 was characterised by the growth of the output and strengthening of the position in economic rankings. The years 2004−2007 can be described as a period of rapid development of the company. In years 2007−2009 the growth tendencies varied due to the economic crisis in the world. Google involvement in the exchange market in 2004 was the trigger for activating the growth of company’s profited assets which in result positively affected the other factors. Since this improvement in 2004, until 2009 there has been a triple growth of the market value and twelvefold growth of the company’s assets and revenue. Moreover, the profits of the company grew 16 times which moved Google from 904 to 120 position in The Global 2000 Magazine rankings of 2000 biggest companies. According to the presented facts and figures, it can be stated that in the era of globalization, the development of the innovative Google company, similarly to other multinational corporations, will be sustained.